AMERICANIZATION AND CULTURAL IMPERIALISM IN THE AMERICAN HOTEL FRANCHISE CHAIN IN INDONESIA - Ronald Maraden Silalahi; Veny Anindya Puspitasari (Akademi Pariwisata Bunda Mulia, 2022)
Americanization is a socio-cultural condition characterized by the imposition of American culture, traditions, and capitalist economic systems worldwide. In the context of modern colonialism, this is marked by the emergence and proliferation of various American brands or franchises in various locations. This fact is based on the belief that products or services with an American identity are considered to have better quality when compared to companies from other countries. This phenomenon is implicated in the hospitality business chain in Indonesia, which is marked by the large number of American hotels located in Indonesia. This article investigates the phenomenon of Americanization in the American hospitality business chain in Indonesia. This research is qualitative research using a cultural studies approach. The primary data is from interviews with 21 American Hotel guests in Indonesia. The secondary data contains related literature sources with intertextual links with the phenomenon of Americanization. Research that synergizes between cultural studies and applied management in the hospitality sector has not been found in many other studies, so this research is expected to enrich the knowledge base in the socio-cultural and hospitality fields.